2003
DOI: 10.1128/mcb.23.18.6339-6349.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ssu72 Protein Mediates Both Poly(A)-Coupled and Poly(A)-Independent Termination of RNA Polymerase II Transcription

Abstract: Termination of transcription by RNA polymerase II (Pol II) is a poorly understood yet essential step in eukaryotic gene expression. Termination of pre-mRNA synthesis is coupled to recognition of RNA signals that direct cleavage and polyadenylation of the nascent transcript. Termination of nonpolyadenylated transcripts made by Pol II in the yeast Saccharomyces cerevisiae, including the small nuclear and small nucleolar RNAs, requires distinct RNA elements recognized by the Nrd1 protein and other factors. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 61 publications
8
131
3
Order By: Relevance
“…This provides a signal for binding many factors involved in 39-end formation, which in turn renders RNAPII competent for termination (Whitelaw and Proudfoot 1986;Logan et al 1987;Connelly and Manley 1988;Birse et al 1997;. In yeast, mutations and conditional depletion of factors involved in pre-mRNA cleavage and polyadenylation, including homologs of CstF-64 (Rna15), CstF-77 (Rna14), Pcf11, CPSF160 (Yhh1), CPSF-73 (Ysh1), and Ssu72, result in read-through at the 39-end of protein-coding genes (Birse et al 1998;Dichtl et al 2002;Steinmetz and Brow 2003;Garas et al 2008). Accordingly, ChIP assays suggest that 39-end processing factors, including Pcf11, Rna14, and Rna15, become associated with the RNAPII EC at the poly(A) site, in a Ser2 phosphorylated CTD-dependant manner (Ahn et al 2004;Kim et al 2004a;Luo et al 2006).…”
Section: Trans-acting Factor Dynamics At the Poly(a) Site Affect Tranmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides a signal for binding many factors involved in 39-end formation, which in turn renders RNAPII competent for termination (Whitelaw and Proudfoot 1986;Logan et al 1987;Connelly and Manley 1988;Birse et al 1997;. In yeast, mutations and conditional depletion of factors involved in pre-mRNA cleavage and polyadenylation, including homologs of CstF-64 (Rna15), CstF-77 (Rna14), Pcf11, CPSF160 (Yhh1), CPSF-73 (Ysh1), and Ssu72, result in read-through at the 39-end of protein-coding genes (Birse et al 1998;Dichtl et al 2002;Steinmetz and Brow 2003;Garas et al 2008). Accordingly, ChIP assays suggest that 39-end processing factors, including Pcf11, Rna14, and Rna15, become associated with the RNAPII EC at the poly(A) site, in a Ser2 phosphorylated CTD-dependant manner (Ahn et al 2004;Kim et al 2004a;Luo et al 2006).…”
Section: Trans-acting Factor Dynamics At the Poly(a) Site Affect Tranmentioning
confidence: 99%
“…2; Fatica et al 2000;Morlando et al 2002;Steinmetz and Brow 2003;Steinmetz et al 2006a). Both terminators are required for efficient termination.…”
Section: The Nrd1 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the four kinases, there are two known CTD phosphatases in yeast, . Biochemical as well as genetic evidence indicates that both proteins may function as CTD phosphatases in the context of transcription (16,19,20,(25)(26)(27)(28)(29)(30)(31).It is the interplay between these CTD kinases and phosphatases that influences which factors associate with transcribing polymerase and when during the transcription cycle such associations occur. As mentioned, the recruitment of capping enzyme early in the transcription cycle is believed to be one consequence of CTD phosphorylation on Ser5 by Kin28 (6,7).…”
mentioning
confidence: 99%
“…In fact, Ssu72 was originally identified as functionally interacting with the general transcription factor TFIIB [184][185]. Afterward, it was demonstrated that Ssu72 is part of the cleavage and polyadenylation factor (CPF) with a role at the 3'-end of genes [166,175]. In fact, Ssu72 is crucial for transcription-coupled 3'-end processing and termination of proteincoding genes [175,[186][187].…”
Section: Ssu72mentioning
confidence: 99%